Effect of nitriding on fatigue life of the cylinder block for two-stroke engine - Nor Azinee, Said (2008)
Aluminum alloys are one of the most capable material selections for automobiles parts and electrical component to reduce their weight and to increase their specific strength. This project report describes the role of nitriding process on fatigue life of the cylinder block for a two-stroke internal combustion engine. The objectives of this project are to predict the fatigue life of cylinder block using stress-life, to identify the critical location, toinvestigate the effect nitriding process and to optimize cylinder block’s material. The structural model of cylinder block was developed using the computer aided design software. The finite element modeling and analysis were performed utilizing finite element analysis code. The set of aluminum alloys is consider in this study. The three-dimension solid model was imported to the MSC.PATRAN software and employed to generate meshes and define material properties for finite element modeling. The finite element analysis was performed using MSC.NATRAN code. The finite element model of component was analyzed using the linear elastic approach. The fatigue life analysis was carried out using MSC. FATIGUE software. Fatigue stress-life approach was used and sensitivity analysis on fatigue life is discussed. Stresses obtained previously are employed as input for the fatigue life. From the result, it was shown that the Goodman mean stress correction method is predicted more conservative (minimum life) results. It was found to differ considerably the compressive and tensile mean stresses to give noticeable advantages and fond to be design criteria. Based on the finite result, it is observed that the nitrided treatment produces longest life for all loading conditions. Therefore, the nitriding process is one of the promising surface treatments for aluminum alloy part to increase the fatigue life of the linear engine cylinder block.